PEMAHAMAN MASYARAKAT TERHADAP KEBEBASAN BERPENDAPAT DALAM PRESPEKTIF HAK ASASI MANUSIA DIERA DIGITAL (DESA CARITA KECAMATAN CARITA KABUPATEN PANDEGLANG) - Sa'adiyyah, Ade Millatus; Agustin Maharani, Anisda (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2025)
In this very rapid tecnological development, technology and information related to human fredoom of opinion have greatly resulted in the development of the implementation of fredoom of opinion through social media, where this often creates tension in the dynamics of society. In the era of digital social media, it is a forum for accommodating sugestions and opinions, but the exitence of this social media also causes problems among society. The problems on social media are problems that are contrary to legal teachings fake news or what is usually called hoaxes, using SARA to makle fun, defamation, exspressing hatred, and not being responsible when using social media. Therefore, this research took determine the publics understanding of defamation in the digital era. this research took place in Carita Village, Carita District, Pandeglang Regency using analytical methods. The results of this research concluded that the public still does not ubderstand the meaning of the right to opinion and defamation in digital land, this is due to the lack of govermnet outreach to provide understanding to the public. Apart from that it reduces the level of public education which access to learning in understanding reputation pollution on social media. The goverments role is important in providing out reac regarding the limits of freedom of speech and opinion so that people do not fall into defamation, sepecially on sosial media.